Hubungan Pengetahuan, Kepercayaan dan Sikap Masyarakat Pesisir Pantai Kota Mataram dengan Perilaku Penerapan Protokol Kesehatan pada Era New Normal - Zubair, M. Abdul Hamid; Supingato, Agus; Hadi, Irwan; Arifin, Zaenal (Master of Epidemiology, Faculty of Public Health, Diponegoro University, Indonesia, 2024)
Background: The implementation of health protocols in the new normal era is still not applied to the maximum, this is feared that it can cause a new cluster of Covid 19 spread. The purpose of this study is to know the factors related to people's behavior in implementing health protocols.Methods: This research design uses a correlational analytic design with a Cross Sectional approach. The study sample of 103 respondents used Purposive sampling techniques. Data collection using questionnaires that have been tested for validity and reliability. The data was analyzed using the spearman rank correlation test.Result: The results of this study showed a significant relationship between attitudes and public behavior in implementing health protocols with a value of 0.02<0.05.Conclusion : The better the attitude of the community, the better the behavior of the community in implementing health protocols. There needs to be a role for health workers to improve the socialization of Covid 19 prevention, so that it has an impact on good community behavior in implementing health protocols.